Emergence of Ebola Virus Disease (EVD): Key Facts - Rahman, Md Mahfuzar; Mehrin, Farnaz; Ahmed, Fahim (Anwer Khan Modern Medical College Journal, 2015)
The modern emerging infection Ebola Virus Disease (EVD) is of global threat originates from Africa region. This is zoonotic and identified as human diseases or previously called Ebola hemorrhagic fever which is a highly fatal human illness where case fatality rate is found up to 90%. The virus transmission begins from wild animals to human and then spreads within population through human to human. Fruit bats are found as natural host of Ebola virus. There is no specific treatment or vaccine available in the market so far, intensive supportive care is needed for severely ill patients. This paper highlights background information, problem statement, viral characteristics, mode of transmission, signs and symptoms, prevention & vaccination. It also indicates possible actions towards prevention of transmission & personal protection. Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 35-37